Identitetni izzivi in družbene izkušnje študentov in študentk z ovirami - Ule, Mirjana (Družboslovne razprave, 2013)
The paper focuses on the experiences and experiencing of handicap, policies of self-understanding as well as the life plans and aspirations of students with disabilities. In the article, we draw on the results of a qualitative survey of students with disabilities who are studying at various faculties of the University of Ljubljana. The research results show that students with disabilities are able to reshape their identities in a way which does not consist of the experienced disability but is independent of it and are capable of accepting their disability as a reality of their own life, without losing a sense of their own purpose of life and life plans. This experience is a significant part of the identity formation of people with disabilities and the precisely produced social experience of people with disabilities strengthens their selfhood and creates new responses and challenges to the contemporary dilemmas of identity formation and identity policies.
Keywords: Students; Študentje; Identiteta (Psihologija); Identity (Psychology); Social policy; Socialna politika; Slovenia; Slovenija; hendikep